Productivity Response to a Contract Change - Rajshri Jayaraman; Debraj Ray; Francis de Véricourt (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper studies the productivity impact of a contract change for tea pluckers in an Indian plantation. The contract, implemented at the end of a three-year cycle in which contracts are generally revised, was (a) the joint outcome of negotiations between twenty unions and plantations, (b) mandated to respect a state government notification stipulating a new minimum wage for plantation workers statewide, and (c) applicable equally to all the plantations in the local region. The contract raised the baseline wage by 30% but lowered marginal incentives, by shifting the existing piece rates to higher minimum thresholds and eliminating an existing penalty per unit for low output. In the one month following the contract change, output increased by a factor between 30-60%, the exact number depending on the choice of counterfactual and the set of controls applied. This large and contrarian response to a flattening of marginal incentives is at odds with the standard model, including one that incorporates dynamic incentives, and it can only be partly accounted for by higher supervisory effort. We conclude that the increase is a "behavioral" response. Yet in subsequent months, the increase is comprehensively reversed. In fact, an entirely standard model with no behavioral or dynamic features that we estimate off the pre-change data, fits the observations four months after the contract change remarkably well. While not an unequivocal indictment of the recent emphasis on "behavioral economics," the findings suggest that non-standard responses may be ephemeral, especially in employment contexts in which the baseline relationship is delineated by financial considerations in the first place. From an empirical perspective, therefore, it is ideal to examine responses to a contract change over an substantial period of time.
Keywords: J43; 330; incentive pay; personnel economics; productivity; contracts